Bismuth phosphinate incorporated nanocellulose sheets with antimicrobial and barrier properties for packaging applications. (10th February 2020) - Maliha, Maisha; Herdman, Megan; Brammananth, Rajini; McDonald, Michael; Coppel, Ross; Werrett, Melissa; Andrews, Philip; Batchelor, Warren
Abstract: The incorporation of an organobismuth complex into a nanocellulose matrix to develop a free-standing antimicrobial barrier material was investigated. The non-toxic complex, phenyl bismuth bis (diphenylphosphinato) was used as the additive to impart antimicrobial properties to nanocellulose sheets for the development of paper-based renewable and biodegradable active packaging material. A spraying technique was used to prepare sheets with different loadings of the organobismuth complex and its effects on antimicrobial and barrier properties were studied. Morphological studies of the sheets revealed the overall distribution of the complex throughout the nanocellulose matrix, with occasional clustering behaviour on the surface. Water vapour permeability of the paper sheets increased very slightly with loading of the bismuth complex, but remained in the range acceptable for packaging materials. The physical and mechanical properties of the sheets were also affected by the addition of the bismuth complex in the structure, and hence a trade-off needs to be made between the loading level and the material performance for commercialization. The composite sheets were able to inhibit the growth of bacteria and fungi, including strains of multidrug resistant bacteria. Moreover, the paper showed continued release of the bismuth complex over time with effective lifetime depending on the loading. In summary, this paper describes the preparation and characterization of a sustainable and ecofriendly antimicrobial composite paper, using a poorly soluble bismuth complex dispersed into a nanocellulose matrix, which shows the potential to be used as an active packaging material. Graphical abstract: Image 1 Highlights: Nanocellulose composites with varying bismuth complex content were developed. The physical, mechanical and barrier properties against water vapour were studied. Bismuth complex has little effect on barrier property unless present at high level. Composites can inhibit the growth of medically important bacteria and fungi. Composite are more effective on Gram-positive bacteria, even at very low loading.